The written texts production and correction in pandemic times: is it about the use of technologies or is it about the possibilities of promoting an integral human formation - Thessing, Aline Francieli; Garcia, Daniela Cristina da Silva; Lima, Phelippe Rave Soares de (Revista Letras Raras, 2021)
In this article, from a marked conception of Linguistic Education (BRITTO, 2012) and, therefore, from a work with the production and correction of texts that focuses on the development of the subjects that are part of the teachinglearning process, we seek to debate the limits and possibilities imposed on the work of the Portuguese language teacher, with specific attention to the written textual production, given the establishment of Remote Education in response to the emergency imposed by the global pandemic of the Sars-CoV-2 virus. For that, we will present in the following subsections a discussion about the conceptions of textual production, the possibility of dialogue with the student through the text as a space that aims to promote a project of saying, keeping in mind a correction to human formation. We hope, with this work, to contribute to a Portuguese language teacher with regard to teaching and learning of language in school contexts.